1999
DOI: 10.4141/a99-032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maturity of silage and protein content of concentrates on milk production of ewes rearing twin or triplet lambs

Abstract: . 1999. Effects of maturity of silage and protein content of concentrates on milk production of ewes rearing twin or triplet lambs. Can. J. Anim. Sci. 79: 499-508. Fifty-one Outaouais Arcott ewes were used to study the effects of silage maturity, protein level and number of lambs suckled on milk production and lamb growth in a 2 × 2 × 2 factorial design experiment. Ewes were given ad libitum access to either an early-bloom (EB) or full-bloom (FB) bromegrass silage supplemented with 725 g d -1 of a 15 or 21% CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Gallo and Davies (1991) reported that in the first month of lactation intakes of triplet-bearing ewes rearing either two or three lambs did not differ. Combined these results indicate that a triplet-rearing ewe is more likely to be under nutritional stress in lactation than twin rearing ewes and therefore it is not surprising that triplet-rearing ewes lose more body condition (Gallo and Davies 1988;Roy et al 1999;Alexandre et al 2001;Kenyon et al 2010a;Hutton et al 2011). Further, Kenyon et al (2013) noted that triplet dams rearing a full set of triplets had lower body condition and live weight at weaning than a ewe rearing only one or two of their triplet lambs.…”
Section: Lamb Growthmentioning
confidence: 90%
See 3 more Smart Citations
“…Gallo and Davies (1991) reported that in the first month of lactation intakes of triplet-bearing ewes rearing either two or three lambs did not differ. Combined these results indicate that a triplet-rearing ewe is more likely to be under nutritional stress in lactation than twin rearing ewes and therefore it is not surprising that triplet-rearing ewes lose more body condition (Gallo and Davies 1988;Roy et al 1999;Alexandre et al 2001;Kenyon et al 2010a;Hutton et al 2011). Further, Kenyon et al (2013) noted that triplet dams rearing a full set of triplets had lower body condition and live weight at weaning than a ewe rearing only one or two of their triplet lambs.…”
Section: Lamb Growthmentioning
confidence: 90%
“…In addition, the number of lambs weaned within a triplet set can negatively affect individual lamb weaning weights (Table 4), although total weaning weight of a litter is highest when all three lambs are weaned. There is greater variation in litter weaning weight in triplets than twins (Roy et al 1999). Further, Kenyon and Blair (2014) and Gholizadeh and Ghafouri-Kesbi (2015) reported that triplets can be lighter than singletons and twins to at least one year of age.…”
Section: Lamb Growthmentioning
confidence: 97%
See 2 more Smart Citations
“…Percentage of protein in milk did not follow this trend and was also not significantly different among the 4 diets. Milk protein content was shown in one study not to be affected by crude protein concentration in the feed consumed by ewes ( Roy et al., 1999 ). There was not a significant difference in milk urea nitrogen (MUN) concentration among the different diets ( P > 0.05), but there was a trend for diets with grass hay as the forage to have higher MUN.…”
Section: Resultsmentioning
confidence: 99%